2019
DOI: 10.1002/anie.201813523
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis with Palladium Complexes Photoexcited by Visible Light

Abstract: Palladium catalysis induced by visible light is an emerging field of catalysis. In contrast to classical reactions catalyzed by Pd complexes in the ground state, which mostly proceed through two‐electron redox processes, the mechanisms of these new methods based on photoexcited Pd complexes usually operate through transfer of a single electron. Such processes lead to putative hybrid Pd/radical species, which exhibit both radical and classical Pd‐type reactivity. This Minireview highlights the recent progress i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(109 citation statements)
references
References 76 publications
1
95
1
Order By: Relevance
“…This could be the possible reason for higher selectivity when BINAP was employed in this system. Again, cyclic (19, 21, 23), heterocyclic (18,19) and acyclic (24)(25)(26)(27)(28)(29), difluorinated (20), indane (22) moieties smoothly participated in the cross-coupling reaction. A broad range of functional groups such as trifluoromethyl (5), amides (12, 16, 18), ethers (13,17) and esters (6,15) were found to be compatible.…”
Section: Entrymentioning
confidence: 98%
See 1 more Smart Citation
“…This could be the possible reason for higher selectivity when BINAP was employed in this system. Again, cyclic (19, 21, 23), heterocyclic (18,19) and acyclic (24)(25)(26)(27)(28)(29), difluorinated (20), indane (22) moieties smoothly participated in the cross-coupling reaction. A broad range of functional groups such as trifluoromethyl (5), amides (12, 16, 18), ethers (13,17) and esters (6,15) were found to be compatible.…”
Section: Entrymentioning
confidence: 98%
“…18 However, recent breakthroughs in photoredox chemistry, [19][20][21] have shown that photoexcited palladium catalysts can be used to generate open-shell species from alkyl halide precursors. 22 Thus, we questioned whether -allylpalladium complexes could also be generated through a single-electron transfer (SET) mechanism to overcome the aforementioned limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the pioneering works on visible-light induced Pdcatalyzed alkyl-Heck coupling reactions, 11 we envisioned that photoirradiation might facilitate the SET event between Pd(0) complex and Dowd-Beckwith halides to initiate the ring expansion process. The interaction of the tertiary radical species and Pd(I) complex generated in situ would provide opportunities for further transformation (Scheme 1, eqn b).…”
Section: Resultsmentioning
confidence: 99%
“…[33][34][35][36] Recently, photocatalytic selective organic transformations [37][38][39][40][41] including homogenous photocatalyzed C-C cross-coupling reactions under visible-light have attracted much interest. [42][43][44][45][46][47][48][49][50][51][52][53] Heterogeneous catalytic systems 42,[54][55][56][57][58][59][60] for C-C cross-coupling reactions have been reported in smaller numbers. Ligand-free palladium catalysed cross-couplings in general require higher temperatures.…”
Section: Introductionmentioning
confidence: 99%